2014
DOI: 10.1016/j.biocel.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Non-tumorigenic epithelial cells secrete MCP-1 and other cytokines that promote cell division in breast cancer cells by activating ERα via PI3K/Akt/mTOR signaling

Abstract: Efforts in understanding the role of the microenvironment in the development of breast cancer have focused on tumor-stroma cross-talk, but the possibility that normal epithelial cells might also play a role in tumor progression has received little attention. Here, we show that non-tumorigenic human mammary epithelial cells (MCF10A and HMEC) secrete factors able to enhance the proliferation of estrogen receptor α (ERα) positive breast cancer cells (MCF7 and T47D) and suppress their ability to undergo apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…A decreased expression of COL6A3 (Collagen IV) was involved in the inflammation‐resistance process and helped to increase the content of triglyceride while promoting lipolysis and the phosphorylation of Akt . By inhibiting MCP1 expression, the PI3K/Akt signaling pathway was downregulated, thus leading to the promotion of the tumor cell apoptosis process . Additionally, Kim et al observed that THBS2 influences the proteolysis of tumor cytoplasm, thus contributing to the activation and expression of certain proteins in the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased expression of COL6A3 (Collagen IV) was involved in the inflammation‐resistance process and helped to increase the content of triglyceride while promoting lipolysis and the phosphorylation of Akt . By inhibiting MCP1 expression, the PI3K/Akt signaling pathway was downregulated, thus leading to the promotion of the tumor cell apoptosis process . Additionally, Kim et al observed that THBS2 influences the proteolysis of tumor cytoplasm, thus contributing to the activation and expression of certain proteins in the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There is feasible evidence that ligation of MCP-1/CCL2 to CCR2 could be linked to PI3K/AKT/mTOR signaling. 30,31 We, therefore, first checked their activity by Western blot analysis. Indeed, loss of Ccr2 resulted in a significant reduction for the phosphorylated PI3K/AKT/mTOR, and even total levels for PI3Kp85 and mTOR were lower compared with that of WT mice after UUO induction.…”
Section: Discussionmentioning
confidence: 99%
“…To further dissect the molecular mechanisms by which loss of Ccr2 repressed VEGF-C expression in macrophages to attenuate UUO-induced lymphangiogenesis, we checked with the focus on the PI3K-AKT-mTOR pathway. 30,31 We first established that the infiltrated macrophages by UUO induction expressed high levels of CCR2 (Supplemental Figure S4). Western blot analysis was then performed to examine the PI3K-AKT-mTOR signaling.…”
Section: Loss Of Ccr2 Represses Pi3k-akt-mtor Signaling Along With Rementioning
confidence: 99%
“…6 mTOR is a kinase that is activated by phosphorylation in response to growth factors and other nutrients and regulates cell growth. [7][8][9] Eukaryotic translation initiation factor 4E binding protein I (4EBP1) and 70-kDa ribosomal protein kinase I (p70) are downstream effectors of mTOR, which activate translation and protein synthesis and cause cell proliferation. 10,11 Studies show that mTOR acts as a nutrient sensor and correlates with the proliferation of trophoblast cells and may contribute to first trimester trophoblast invasion.…”
Section: Introductionmentioning
confidence: 99%